Disparate effects of four anions on the non-radical oxidation process of sulfamethoxazole by peroxymonosulfate: kinetics, mechanism and toxicity variation. Issue 3 (June 2022) - Sun, Yanlong; Li, Yu; Zhan, Jianmin; Feng, Aiqi; Zhou, Chengzhi; Chen, Jianrong
Abstract: In the present work, the impact of four anions (Cl -, HCO3 - CO3 2- and PO4 3- ) on sulfamethoxazole (SMX) degradation during in suit chemical oxidation by peroxymonosulfate (PMS) was investigated. Results shows that the degradation of SMX follows a two-phase kinetic model (fast stage and slow stage), and the degradation efficiency is enhanced by the four anions. Based on transient species determination, theoretical calculation and intermediate identification, the fast stage for SMX degradation may be caused by direct oxidation of PMS, and the slow stage is involved with reaction with singlet oxygen and peroxoanion radical. The site reaction with peroxoanion radical is nitrogen-oxygen bond in five-membered heterocycles. Ecological risk of degradation products in the absence of four anions is higher than the parent compound, accompanying with Escherichia coli death cell increasing from 51.7% to 91.6%. In the presence of Cl -, the dead cell percentage further increases to 93.3% due to the generation of chlorinated derivatives. On the contrast, HCO3 - CO3 2- and PO4 3- can alleviate the dead cell percentage to 26.4%, 24.4%, and 17.9%, respectively. These results suggest that the anion plays an important role in the degradation of organic pollutants by PMS technology. Graphical Abstract: ga1 Highlights: The degradation of SMX oxidized by PMS follows a two-phase kinetic model. Degradation efficiency of SMX is enhanced by four inorganic anions. Mechanism involves direct oxidation, reaction with 1 O2 and peroxoanion radical. Potential risks caused by intermediates decreased in the presence of oxyanions.